Model Dick And Carey Sebagai Pendekatan Sistematis Dalam Pembelajaran Pendidikan Agama Islam - Saputra, Indrian; Anita, Fitri (Varied Knowledge Journal, 2025)
This study aims to describe the application of the Dick and Carey model in Islamic Religious Education (PAI) learning on obligatory prayers for grade III elementary school students. This study uses a descriptive qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the Dick and Carey model is applied systematically through ten steps including identification of learning objectives, learning analysis, analysis of student characteristics, and evaluation planning. Teachers carry out learning according to the stages of instructional design and make revisions based on formative evaluation. Summative evaluation is carried out through written tests and direct prayer practice. The application of this model has proven effective in improving students' understanding and skills in performing obligatory prayers. Learning becomes more structured, focused, and able to balance students' cognitive, affective, and psychomotor aspects. Keywords: Dick and Carey Model, PAI Learning, Learning Evaluation.